ANALISIS PEMAHAMAN KONSEP PESERTA DIDIK PADA MATERI GERAK LURUS BERUBAH BERATURAN DI SMA - Gita Fransiska; Edy Tandililing; Muhammad Musa Syarif Hidayatullah (Universitas Tanjungpura, 2022)
AbstractThe study aims*to identify students’ concepts understanding in the material of uniformly changing straight motion in SMA Negeri 1 Tanah Pinoh. The study used a survey method without a comparison class that is descriptive correlative. The research instrument was a multiple-choice diagnostic test with three answer choices, ten questions were about conceptual understanding, and ten questions were about learning outcomes test. The validation of the*learning outcomes test was 3.36 with valid criteria, while the reliability of the learning outcomes test was 0.44 with the medium category. The result found that the students’ concepts understanding was classified low with an*average percentage of 31.39%. The students’ concepts understanding with the highest percentage is in the interpretation aspect of 41.67% with a sufficient category, and the minor percentage is in exploration aspects with 31.39%. The study did not find a correlation of rcount 0,360 < rtable 0,179 between conceptual understanding and learning outcomes. Therefore, the understanding concept becomes an essential principle for achieving physics learning outcomes. The study also found that there had not been any difference among gender as indicated by the results of the MannWhitney test (P> 0.05), with the analysis results showing that female students were higher than male students in the aspects of translation and extrapolation. While, in the interpretation aspects, male students are higher than female students. Thus, the results of this study are expected to be a consideration for determining the learning model to improve students' concepts understanding.Keywords: Concept Understanding, Gender, Learning Outcome.